1988
DOI: 10.1177/00220345880670120401
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 1% Pyrophosphate and 0.02% Sodium Fluoride on Artificial Caries Lesions in vivo

Abstract: We evaluated the potential of a pyrophosphate-fluoride solution to affect the remineralizing-demineralizing equilibrium, i.e., caries-inhibiting/-promoting effects on enamel in vivo. Fifteen subjects carried dentin blocks and enamel thin sections with artificial caries lesions in removable partial dentures for periods of two weeks, during which time they rinsed twice daily in a double-blind, randomized cross-over design with solutions containing (a) 90 ppm F, (b) 90 ppm F and 1% pyrophosphate, or (c) no active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Using single sections, which are measured longitudinally with repositioning, the lesion at the original assessment site (as outlined above), the effect of intra-lesion variation can be minimised [Stephen et al, 1992;Exterkate et al, 1994]. Others have used multiple sec tions per panellist which are analysed individually and then averaged to generate the panellist's average response to a treatment [Mellberg et al, 1988;Stephen et al, 1992],…”
Section: A Comparison Of Lesion Preparation Andmentioning
confidence: 99%
“…Using single sections, which are measured longitudinally with repositioning, the lesion at the original assessment site (as outlined above), the effect of intra-lesion variation can be minimised [Stephen et al, 1992;Exterkate et al, 1994]. Others have used multiple sec tions per panellist which are analysed individually and then averaged to generate the panellist's average response to a treatment [Mellberg et al, 1988;Stephen et al, 1992],…”
Section: A Comparison Of Lesion Preparation Andmentioning
confidence: 99%
“…The thin-section sandwich method, which has been described in detail in several previous publications [Mellberg et al, 1986[Mellberg et al, , 1988, was used. Thin sections of polyacrylate-embedded sound enamel, approximately 100 pm thick, were secured with cyanoacrylate adhesive between two thin pieces of polyester plastic for support and to prevent mineral exchange from occurring on the cut faces of the section.…”
Section: Evaluation Of Remineralizationmentioning
confidence: 99%
“…Because pyrophos phate functions to inhibit calculus formation by inter fering with the formation and growth of crystal nuclei in plaque [McGaughey, 1983], it has the potential of interfering with the natural anticaries mechanism of remineralization. Previous studies, however, have shown that 3.3% pyrophosphate in fluoride dentifrice formulations does not interfere with remineralization in situ [Mellberg et al, 1987] nor does 1% pyrophos phate in a mouthrinse [Mellberg et al, 1988]. Sim ilarly, pyrophosphate did not adversely affect the an ticaries effect of fluoride in a rat caries model [Spak et al, 1988].…”
mentioning
confidence: 97%
“…It is evident that fluoride is very effec tive in preventing demineralization in all but very shallow lesions and that in situ experimental use of shallow lesions may result in net demineralization, even when a fluoride treatment is given. Subsequent examination of the baseline lesion size in two previ ously reported studies [Mellberg et al, 1988;Deutch- It is also apparent that selection of a relatively nar row range of baseline lesion size should result in re duced variation, and furthermore, if the range is near er the shallow than the deep range, the difference be tween treatments should be greater and, therefore, easier to detect. If large lesions are used, the differ ence between placebo and positive control or test products might be very small, unless, perhaps, a con siderably longer treatment period was used.…”
mentioning
confidence: 99%